Trypanosoma cruzi extracellular amastigotes trigger the protein kinase D1‐cortactin‐actin pathway during cell invasion. (16th July 2015) - Bonfim‐Melo, Alexis; Zanetti, Bianca Ferrarini; Ferreira, Éden Ramalho; Vandoninck, Sandy; Han, Sang Won; Van Lint, Johan; Mortara, Renato Arruda; Bahia, Diana
Summary: T rypanosoma cruzi extracellular amastigotes (EAs) display unique mechanisms for cell invasion that are highly dependent on host actin filaments. Protein kinase D1 (PKD1) phosphorylates and modulates the activity of cortactin, a key regulator of actin dynamics. We evaluated the role of host cortactin and PKD1 in actin filament dynamics during HeLa cell invasion by EAs. Host cortactin, PKD1 and actin are recruited by EAs based on experiments in fixed and live cells by time lapse confocal microscopy. EAs trigger PKD1 and extracellular signal‐regulated kinase 1/2 activation, but not Src family kinases, and selectively phosphorylate cortactin. Heat‐killed EAs and non‐infective epimastigotes both triggered distinct host responses and did not recruit the molecules studied herein. EA invasion was influenced by depletion or overexpression of host cortactin and PKD1, respectively, suggesting the involvement of both proteins in this event. Collectively, these results show new host cell mechanisms subverted during EA internalization into non‐phagocytic cells.